Ice Jams, Winter 2000-2001. Ice Engineering. Number 12, December 2001 - Furman, Linnzi; White, Kate (2001)
During winter months, rivers, lakes, and streams freeze in cold regions. Ice jams form during initial ice cover formation as the ice accumulates, restricting water flow (freezeup jam), and also form when the ice cover breaks up and clogs the river downstream (breakup jam). When the river becomes jammed with ice, backwater flooding can cause costly damage to low-lying areas and municipal structures. Riverine communities upstream of the jam can suffer severe effects as a result of backwater flooding. Communities downstream of the jam can also be affected by a rapid surge of water and ice that is released when a jam breaks. Because it is difficult to predict when jams will occur or release, there is little time to prepare for flooding. Bridges, roads, and buildings often are damaged by the resulting excessive water and ice. Roads and runways can be forced to close, and bridges can be damaged or destroyed, delaying or limiting emergency medical aid in evacuation situations. Transportation of heating fuel and other necessary cargo can be temporarily halted. The original document contains color images.